Evaluation of striped catfish, Pangasius hypophthalmus (Sauvage, 1878) dried viscera and its intestinal putative probiont on juvenile African catfish, Clarias gariepinus (Burchell, 1822) growth performance - Abu Bakar, Siti Nadia; Mohd Daud, Hassan; O., Jintasataporn; Abu Hassim, Hasliza; Abd Karim, Murni Marlina; Hamid, Nurhidayahanum; Mohamed Yusoff, Siti Fairus (AkiNik Publications, 2019)
The growth performance of juvenile African catfish, Clarias gariepinus were evaluated after feeding with striped catfish, Pangasius hypophthalmus dried viscera and its intestinal putative probiont. The chosen isolated putative probiont were identified as Weissella sp. through 16S rDNA sequence analysis. Utilization of dried striped catfish viscera as well as Weissella sp. as supplementation in African catfish diet show better growth performance in compare to the unsupplemented treatment. At the end of experiment, fish fed with Weissella sp. (T3) showed significantly high growth performance (P<0.05) in terms of its body weight, body weight gain, average daily gain and specific growth rate when compared to control (T1), but exhibited no significant difference (P>0.05) with T2. Furthermore, histological assessment of intestinal villi height of T3 shows significantly longer (P<0.05) than other two treatments. Hence, African catfish diet composed of probiont, Weissella sp. suspension at dosage of 109 cfu/ml diet (T3) was recommended to promote C. gariepinus growth performance.